2003
DOI: 10.1046/j.1365-3040.2003.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

The case for cytosolic NO3 heterostasis: a critique of a recently proposed model

Abstract: -homeostasis, as determined by microelectrodes, is at odds with certain experimental observations, they nevertheless promote a model that takes microelectrode readings at face value, and assert that the variations seen using CATE methodology are artefacts attributable to contributions from substantial, rapidly exchanging, and highly variable NO 3 -pools putatively residing in organelles such as plastids and the endoplasmic reticulum. We show here that such a model is not tenable, drawing upon experimental evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…This conclusion is consistent with physiological studies indicating that root NO 3 À efflux, in contrast with NO 3 À influx, is a thermodynamically downhill process (reviewed in Crawford and Glass, 1998;Miller et al, 2007). Moreover, although the extent of the cytosolic NO 3 À pool is debated (Britto and Kronzucker, 2003), the K m value of the NAXT system observed in vitro is consistent with the range of cytosolic NO 3 À values recently observed by different methods in well-supplied plants (Radcliffe et al, 2005;Ritchie, 2006).…”
Section: A Molecular Basis For Passive No 3 2 Efflux Activity At the supporting
confidence: 91%
“…This conclusion is consistent with physiological studies indicating that root NO 3 À efflux, in contrast with NO 3 À influx, is a thermodynamically downhill process (reviewed in Crawford and Glass, 1998;Miller et al, 2007). Moreover, although the extent of the cytosolic NO 3 À pool is debated (Britto and Kronzucker, 2003), the K m value of the NAXT system observed in vitro is consistent with the range of cytosolic NO 3 À values recently observed by different methods in well-supplied plants (Radcliffe et al, 2005;Ritchie, 2006).…”
Section: A Molecular Basis For Passive No 3 2 Efflux Activity At the supporting
confidence: 91%
“…The cytoplasmic nitrate concentrations deduced here are consistent with studies using several types of NO 3 − ‐sensitive microelectrodes (Miller & Zhen, 1991; Zhen et al ., 1991, 1992), estimates based on nitrate reductase activity (King et al ., 1992), and the failure of 14 N‐NMR to detect a cytoplasmic nitrate pool (Belton et al ., 1985); but are not consistent with some other interpretations of 13 N compartmentation in barley roots (Siddiqi et al ., 1991). The absolute size of the cytoplasmic NO 3 − pool is so small that it should be sensitive to small net movements of NO 3 − across the plasmalemma or the tonoplast (Clarkson, 1986), and so would be expected to be a labile pool (Britto & Kronzucker, 2003) rather than a set point (Siddiqi & Glass, 2002). Nitrate is, in a sense, a secondary nutrient because it is normally converted to ammonia before being used in biochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, more invasive studies using nitrate-selective microelectrodes appear to show that cytosolic concentrations of nitrate ([NO 3 ) ] cyt ) are invariable (at approximately 3-5 mM) under a wide range of conditions (Zhen et al 1991;Miller and Smith 1996;Van der Leij et al 1998), including time courses over which the induction states of nitrate transport and metabolism are known to vary widely (Minotti et al 1969;Clarkson 1986;Siddiqi et al 1989;Kronzucker et al 1995a). These findings have been taken at face value by many workers in the field, despite the fact that they contradict key observations, especially of the widely recognized phenomenon that nitrate itself serves as the signal for the induction of its own transport and metabolism (MacKown and McClure 1988;Tischner et al 1993;Crawford 1995;Tischner 2000), given that it is likely that this signalling occurs intracellularly, as evidenced by a recent study in Chlamydomonas (Rexach et al 2002;however, Unkles et al 2001 have suggested the possibility of an extracellular nitrate sensor in yeast, and there remains the further, if remote, possibility that an intracellular sensor could be non-cytosolic-see Britto and Kronzucker 2003). Such a function is difficult, if not impossible, to reconcile with a proposed constancy of [NO 3 ) ] cyt prevailing during all stages of induction and de-induction, even long after external nitrate has been withdrawn, and influx has returned to non-induced levels (Siddiqi et al 1989).…”
Section: Cytosolic Turnover Of Inorganic Ions: Implications For Fluxementioning
confidence: 96%